Khairu Ummah dalam Pandangan K.H. Irfan Hielmy - Ahmad Labib Majdi (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2017)
This paper discusses about K.H. Irfan Hielmy and his ideas about khairu ummah. Khairu ummah is a phrase in the Qur'an that shows an ideal society that has three dimensions of amalgam, amr bi al-ma`ruf, nahy `an al-munkar dan tu`minuna billah. Moving on from these descriptions, K.H. Irfan Hielmy seeks to provide a step for the people and nation of Indonesia to bring civilization khairu ummah, so as to erode the nature and bigotry, exclusive and intolerant. With the beginning of Muslims themselves, according to K.H. Irfan Hielmy, the mutual respect between religious people is not just mere wishful thinking. Coupled with the socio-political conditions of the people who were warm discuss the concept of State, decent proposed and put forward ideas that are expected to be moderate concrete and tangible solutions to the sustainability of the Unitary Republic of Indonesia. The realization of khairu ummah is the situation and condition of all people can live together and side by side without any mutual accusations that are now becoming more frequent.Keywords: biography, k.h. irfan hielmy, khairu ummah thought Abstrak Tulisan ini membicarakan tentang K.H. Irfan Hielmy dan pemikirannya tentang khairu ummah. Khairu ummah adalah sebuah frasa dalam al-Quran yang menunjukkan sebuah tatanan masyarakat ideal yang memiliki tiga dimensi amaliah, yaitu amr bi al-ma`ruf, nahy `an al-munkar dan tu`minuna billah. Beranjak dari keterangan tersebut, K.H. Irfan Hielmy berusaha memberikan langkah bagi umat dan bangsa di Indonesia untuk mewujudkan peradaban khairu ummah, sehingga mampu mengikis sifat dan sikap fanatik, ekslusif dan intoleran. Dengan berawal dari umat Islam sendiri, menurut K.H. Irfan Hielmy, maka saling menghormati dan menghargai antar dan intra umat beragama bukan sekedar angan-angan belaka. Ditambah dengan kondisi sosial-politik masyarakat yang tengah hangat membicarakan konsep Negara, layak dikemukakan dan diketengahkan pemikiran-pemikiran moderat yang diharapkan mampu menjadi solusi konkret dan nyata terhadap keberlangsungan Negara Kesatuan Republik Indonesia. Realisasi khairu ummah adalah situasi dan kondisi seluruh masyarakat dapat hidup bersama-sama dan saling berdampingan tanpa ada saling tuding-menuding dan tuduh-menuduh yang kini justru semakin sering dilakukan.Kata Kunci: biografi, k.h. irfan hielmy, pemikiran khairu ummah